2011
DOI: 10.1039/c1dt10501a
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro and in vivo study of a novel zinc complex, zinc N-(2-hydroxyacetophenone)glycinate to overcome multidrug resistance in cancer

Abstract: Multiple drug resistance (MDR) remains a major clinical challenge for cancer treatment. P-glycoprotein is the major contributor and they exceed their role in the chemotherapy resistance of most of the malignancies. Attempts in several preclinical and clinical studies to reverse the MDR phenomenon by using MDR modulators have not yet generated promising results. In the present study, a co-ordination complex of zinc viz., Zn N-(2-hydroxyacetophenone)glycinate (ZnNG) has been synthesized, characterized and its an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…For example, Choudhuri and coworkers developed a series of [M(N-(2-hydroxy acetophenone)glycinate)(H 2 O) n ] complexes, where the M is Fe III (n = 3), 16 Ni II (n = 1), 17 Cu II (n = 3) 18 or Zn II (n = 1). 19 In particular, the Cu II complex was shown to directly interact with P-gp showing potential to reverse P-gp mediated drug resistance. 18 Interestingly, it did not compete for the substrate binding or to verapamil-, vinblastine-and progesterone-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Choudhuri and coworkers developed a series of [M(N-(2-hydroxy acetophenone)glycinate)(H 2 O) n ] complexes, where the M is Fe III (n = 3), 16 Ni II (n = 1), 17 Cu II (n = 3) 18 or Zn II (n = 1). 19 In particular, the Cu II complex was shown to directly interact with P-gp showing potential to reverse P-gp mediated drug resistance. 18 Interestingly, it did not compete for the substrate binding or to verapamil-, vinblastine-and progesterone-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…7). Our ongoing studies in this direction with other structurally similar, nontoxic compounds, e.g., zinc N-(2-hydroxyacetophenone)glycinate [53] and iron N-(2-hydroxy acetophenone) glycinate [35], generating ROS in TAMs, showed that they can modulate the cytokine profile in macrophages temporarily (unpublished results). Therefore, further research is necessary to establish a structure-activity relationship among these structurally similar redox-active compounds.…”
Section: Discussionmentioning
confidence: 87%
“…74,75,81,91,92 It plays a role in the elimination of damaged, aged, and/or mutated cells. 74,75,81,91,92 To further study whether the cell death caused by Zn(TA) (3.04 μM) and Zn(TAC) (0.14 μM) was via apoptosis, we stained A549/DDP cells with 7-AAD, which stains necrotic cells, and annexin V-APC, which detects phosphatidylserine residues translocated from the inner cell membrane to the outer cell membrane in the early apoptotic stages. 72,74,75,81,91,92 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…74,75,81,91,92 To further study whether the cell death caused by Zn(TA) (3.04 μM) and Zn(TAC) (0.14 μM) was via apoptosis, we stained A549/DDP cells with 7-AAD, which stains necrotic cells, and annexin V-APC, which detects phosphatidylserine residues translocated from the inner cell membrane to the outer cell membrane in the early apoptotic stages. 72,74,75,81,91,92 As shown in Fig. 6, 3.04 μM Zn(TA) and 0.14 μM Zn(TAC) induced apoptosis in 31.63% and 66.86% of A549/DDP cells (early + late), respectively; these rates were higher than the apoptosis rate observed (8.28%) in untreated cells.…”
Section: Resultsmentioning
confidence: 99%